PENINGKATAN KEMAMPUAN PRESTASI BELAJAR KELAS 5C MELALUI CANVA PADA MATERI LUAS BANGUN DATAR - Eka Dwi Erlangga; Noor Miyono; Mas’udah; Mudzanatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Using a pre-test and post-test design, this research is descriptive and qualitative. 50% of the students at SDN Bugangan 03 made up the study's population, while 14 students from class 5C served as a sample. Surveys, observations, and interviews were used to gather data. Results from the paired sample t-test showed that H0 was rejected and H1 was accepted, supporting the idea that there was a significant difference between the learning outcomes of the students before and after the intervention, as indicated by a 2-tailed significance value of less than 0.05. Furthermore, with an average N-Gain score of 0.5303, the learning performance test findings from N-Gain categorized the improvement as medium. The study discovered that utilizing Canva as a learning tool improved primary school pupils' learning outcomes in the area of flat figures, with the outcomes also falling into the medium range.